Принцип творческой самодеятельности - Рубинштейн, Сергей (Զանգակ հրատ.)
Real and meaningful learning is a creative process. Skills and knowledge cannot be downloaded like computer software, they must be acquired, constructed and mastered– through long-term application and effort. Those who have studied successful skill mastery describe a common process that is followed, one that requires practice, effort, patience, experimentation and deep concentration. Take the example of language learning. All children are born with the natural ability to learn new languages, they have brains that we might compare to language learning “hardware” in a computer. Over time they master the language of those who surround them, what we might compare to software. But this is where the similarity between computers and humans ends. With a computer you simply transfer the data from one location to another. With human beings new knowledge must be practiced and applied in meaningful situations, so that lasting comprehension and skills develop. Like the body taking in raw materials and transforming them into muscles and bones there is a very organic and constructive process that happens in our brains. Our minds are designed to learn that way. This is why force-feeding decontextualized “knowledge” and then measuring retention with standardized tests is a dead end approach to education. While a computer can retain information that doesn’t mean it understands how to use it. Tests that focus on memorization of data or a narrow range of skills do not measure deep comprehension and mastery. They also fail to assess social and emotional competence, as well as other “soft” skills which are absolutely essential for career and life success. Human beings are not empty containers or machines into which information can just be downloaded in one direction. Practical skills and abilities only develop when learning is interactive, creative and dynamic. Knowledge has to be applied directly and used creatively in meaningful situations.
Keywords: Философия образования